Needs Analysis of ELT Research Methodology Teaching for Undergraduate Students - Muntaha, Muntaha; Kartikawati, Umi (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
This study explores the needs of undergraduate students in learning English Language Teaching (ELT) research methodology, focusing on learners’ perspectives. Employing a quantitative method, data were collected from surveys with 90 undergraduate of English educations students enrolled in the second-level research methodology course, particularly in the areas of instrument design and data analysis. The findings reveal key areas where students face challenges, including limited familiarity with research concepts and a lack of practical experience in conducting studies. Students expressed a strong preference for applying more real-world case studies into the curriculum to make research methodology more engaging and relevant. These findings underline the need for a student-centred approach to teaching ELT research methodology, emphasizing practical skill development and support from the teachers and peers during the project. This study contributes to the field by offering actionable insights for curriculum designers and educators aiming to enhance research methodology instruction for undergraduate ELT students.